A design-centric evaluation of multi-fidelity cost modeling approaches - Scott, R. (My University, 2018)
A new set of cost-estimating relationships is presented in an application-based assessment activity. The assessment conducts a multi-fidelity analysis of aircraft procurement costs on a selection of vehicles using both legacy models and the newly-development methodology. The study compares the overall accuracy of the different approaches as well as the difference in insight yielded by the respective levels of fidelity. The results of the comparison are examined qualitatively in the context of future aircraft development to infer affordability implications pertinent to contemporary design trends and performance requirements.